Graduate Students' Perceptions on Their Metacognitive Awareness in Academic Writing - Kristian Florensio Wijaya (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2021)
Abstract: L2 academic writing processes require both cognitive and affective aspects from EFL University students to be more proficient and independent writers. Hence, metacognitive awareness plays a pivotal role to bridge the huge gap between cognitive and affective elements hindering graduate students to accomplish the given academic writing tasks. Further, this present study attempted to investigate graduate students’ perceptions of their metacognitive awareness in academic writing. To fulfill this study objective, this study was conducted qualitatively by utilizing the qualitative content analysis to provide more obvious portrayals out of the specific events experienced by the participants. Two research instruments were also harnessed in this study namely the Likert-scale Questionnaire and open-ended interview questions. The participants enrolling in this study were 15 English Education Master students of Sanata Dharma University, Yogyakarta having experienced academic writing learning journeys for one and a half years. The obtained findings delineated the importance of cultivating a higher degree of metacognitive awareness during academic writing learning enterprises to make EFL University students more competent, self-regulated, and qualified L2 academic writers. Although this study only contributed a small puzzle piece to complete the prior investigations on the importance of metacognitive awareness in academic writing learning rides, EFL practitioners and educators should foster learners’ metacognitive awareness at the onset of academic writing programs to enrich the development of their cognitive and affective state into the utmost level.   Keywords: metacognitive awareness, academic writing, graduate students